Ayurveda and psychosocial impact of COVID-19 - Tanuja Mehta; Uttam Kumar Sharma; Bhawana Mittal (Wolters Kluwer Medknow Publications, 2020)
Objective: SARS COV-2 is an infectious kind of communicable disease. Where epidemiological triad is formed by environment, agent and host. Along with medical and preventive actions psychosocial intervention for people affected by COVID 19 is equally necessary. Our motive is to find out the role of Ayurveda in managing the psychosocial impact of COVID 19 pandemic. Data Source: For Ayurvedic and modern concepts references have been taken from textbooks, various websites, electronic media and articles. Review Method: Systematic review PRISMA (Preferred Reporting Items For Systematic Reviews and Meta Analyses). Result: Rasayana therapy, Panchakarama procedures, Sadvrit Palan (code of right conducts) and Aachara Rasyana mentioned in Ayurveda can help to manage psychosocial impact of covid 19. Conclusion: Thus, Ayurveda proved to be beneficial in promoting various effective strategies in managing mental and social health in COVID 19.